Effect of Essential Oils Supplemented with Caprylic Acid and Sodium Chloride against Faecal ESBL-Producing Escherichia coli Isolated from Pigs - Daiga Gāliņa; Vitalijs Radenkovs; Jorens Kviesis; Anda Valdovska (MDPI AG, 2022)
The purpose of the present investigation was to compare the antibacterial activity of six commercial and lab-scale extracted essential oils (EOs) alone or in combination with caprylic acid (CA) and sodium chloride (NaCl) against faecal Escherichia coli with and without extended-spectrum beta-lactamase (ESBL) encoding genes, and of isolates classified as multidrug-resistant (MDR). Gas chromatography-mass spectrometry (GC-MS) was used for the analysis of chemical composition of EOs, while the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays were carried out to elucidate the antibacterial activity of non-supplemented and supplemented EOs against different resistance levels of E. coli strains. The main compounds in commercial EOs were aromatic monoterpenoids (30-56%) and p-cymene (8-35%), while the main compounds in the lab-scale EOs were aromatic monoterpenoids (12-37%) and γ-terpinene (18-22%). Commercial EOs exhibited superior inhibitory activity of E. coli in comparison to lab-scale produced EOs. Antibacterial activity of EOs was significantly enhanced by enrichment of the EOs with NaCl (p < 0.001) or CA (p = 0.012). Most of the non-supplemented EOs exhibited lower activity against MDR and ESBL producing E. coli. In contrast, EOs supplemented with CA and especially NaCl was equally effective against ESBL and non-ESBL as well as MDR and non-MDR E. coli. It was found that supplementation of EOs with NaCl could enhance the antibacterial activity towards ESBL and MDR E. coli isolates. However, additional studies are needed to clarify the potential risks of developing resistance.